Prevalence of diaphragm dysfunction in patients with interstitial lung disease (ILD): The role of diaphragmatic ultrasound - Bernardinello, Nicol; Cocconcelli, Elisabetta; Boscolo, Annalisa; Castelli, Gioele; Sella, Nicolò; Giraudo, Chiara; Zanatta, Elisabetta; Rea, Federico; Saetta, Marina; Navalesi, Paolo; Spagnolo, Paolo; Balestro, Elisabetta (Respiratory medicine, 2023)
Diaphragm ultrasound (DUS) has been extensively used in critically ill patients while data on outpatients with interstitial lung disease (ILD) are limited. We hypothesized that diaphragm function, assessed by ultrasound, could be impaired in patients with ILD, considering both Idiopathic Pulmonary Fibrosis (IPF) and Connective Tissue Disease (CTD-ILD), compared to healthy subjects. Moreover, this impairment could impact clinical and functional parameters. All consecutive CTD-ILD and IPF patients followed in our center (March–October 2020) were screened. Diaphragm displacement (DD), inspiratory thickness (Ti), expiratory thickness (Te), thickening fraction (TF), and respiratory functional parameters were collected. The prevalence of diaphragmatic dysfunction (TF <30%) was then recorded. Eighty-two consecutive patients (41 CTD-ILD, 41 IPF) and 15 age- and sex-matched controls were enrolled. In the overall population, 24 out of 82 (29%) presented diaphragmatic dysfunction. In CTD-ILD, DD and Ti were lower as compared to IPF (p = 0.021 and p = 0.036, respectively); while diaphragmatic dysfunction was more prevalent compared to controls (37% vs 7%, p = 0.043). TF positively correlated to patients’ functional parameters in the CTD-ILD group (FVC%pred: p = 0.003; r = 0.45), while not in the IPF group. Diaphragmatic dysfunction was associated with moderate/severe dyspnea in both CTD-ILD and IPF (p = 0.021). The prevalence of diaphragmatic dysfunction was 29% in patients with ILD and was associated with moderate/severe dyspnea. CTD-ILD presented lower DD compared with IPF and a higher prevalence of diaphragmatic dysfunction (TF<30%) compared with controls. TF was associated with lung function only in CTD-ILD patients, suggesting its potential role in the comprehensive patient assessment.